1995
DOI: 10.1002/ajmg.1320570207
|View full text |Cite
|
Sign up to set email alerts
|

Childhood neuronal ceroid‐lipofuscinoses in Argentina

Abstract: We report on 30 cases of neuronal ceroid lipofuscinoses (NCL), mainly diagnosed in 1985-1993 in Argentina, whose population is predominantly of European descent. Twenty-four cases were late infantile Jansky-Bielschowsky (LINCL) and 6 were juvenile Spielmeyer-Vogt (JNCL). Sex ratio was female:male, 20:10. Age range and mean at onset and at diagnosis for the LINCL cases were 1-6 years, mean 3.1, and 2-11 years, mean 5.5, and for the JNCL cases, 5-9 years, mean 7, and 9-18 years, mean 13, respectively. Cases were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 25 publications
0
13
0
1
Order By: Relevance
“…Relatively similar data are reported in the literature [32] with respect to frequency of INCL, LINCL and JNCL. In Italy [33], a Mediterranean population, and in Argentina [34], whose population is predominantly of European descent, the more frequent form seems to be LINCL, representing 63 % and 80 % of NCL cases, respectively. In both populations INCL is very rare.…”
Section: Discussionmentioning
confidence: 95%
“…Relatively similar data are reported in the literature [32] with respect to frequency of INCL, LINCL and JNCL. In Italy [33], a Mediterranean population, and in Argentina [34], whose population is predominantly of European descent, the more frequent form seems to be LINCL, representing 63 % and 80 % of NCL cases, respectively. In both populations INCL is very rare.…”
Section: Discussionmentioning
confidence: 95%
“…The occurrence of 30 cases of NCL disorders was first published in Argentina by Taratuto et al almost 20 years ago (Taratuto et al, 1995). It was later observed that the disease, caused by mutations in the TPP1/CLN2 gene, is prevalent in the region, and genetic findings were published for CLN1 and CLN2 by our group as part of a systematic detection program implemented in Córdoba, Argentina (Kohan et al, 2005; Noher de Halac et al, 2005; Kohan et al, 2009; Kohan, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…56, 64, 92 The mean age of onset of visual loss has been estimated to be between 6.4-6.6 years, 13, 22 with presentation to an ophthalmologist at 5.5-8.5 years (mean 7.3 years). 22 …”
Section: Clinical Presentationmentioning
confidence: 99%